Prendre position face à des auditoires hétérogènes : le cas du stand-up - Ruggero Druetta (Argumentation et Analyse du Discours)
Stand-up, a very popular form of comic performance today, is characterized by a combination of the pragmatic aim of amusing the audience and the overt desire to present the humorous speaker’s standpoint on current affairs, which corresponds to an explicit argumentative aim. However, this is a challenging exercise, both because of the fictional (non-serious) aspect of the comedy show and because of the divisions that the current affairs, whose axiological evaluation is not yet stabilized, could introduce at the thematic and argumentative level within a heterogeneous audience, thereby canceling out the expected euphoric effect. An analysis of some of the argumentative strategies used in the analyzed sketches highlights the importance of the “shown” and “said” ethos and of the interactive dimension of stand-up. It also highlights the crucial role of the enunciative pact that governs this form of performance, granting the stand-up comedian, among other things, the systematic posture of “over-enunciation” (i.e. high-up perspective) in relation to other points of view represented in his discourse.